The Role of The Storytelling Method in Increasing Literacy Interest For Children - Annisa Azzahra; Faridah Faridah; Devi Hertina Panjaitan; Rodia Tammardia Siregar (Journal Analytica Islamica, 2024)
Storytelling is an activity carried out by someone to explain a concept, information, or other mere tales which can be done in writing or orally. This type of storytelling can be done with or without props. Storytelling is a universal communication method that has a big impact on humanity. It can be said that through good stories, children can not only learn about fun or entertainment, but also gain broader education. It is even more accurate to say that stories that highlight various aspects of children's creation and storytelling are an effective way to develop interest in reading. This research uses the Library Research method, namely the study of literature related to research and data collection through surveys. Interest is not an innate factor, but a taught factor. The interest and habit of reading, especially in children, cannot be overcome by itself. Therefore, it is necessary to develop habits and introduce reading. A child's love of reading is greatly influenced by the behavior of his teacher and the people around him. Children who enjoy learning often have teachers and tutors who can help them learn. The desire to learn can be cultivated in children by providing appropriate examples. Children love to imitate the attitudes and behavior of people they admire during their early childhood.